2022
DOI: 10.1155/2022/3699885
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Music Style Classification Based on Deep Learning

Abstract: Music style is one of the important labels for music classification, and the current music style classification methods extract features such as rhythm and timbre of music and use classifiers to achieve classification. The classification accuracy is not only affected by the classifier but also limited by the effect of music feature extraction, which leads to poor classification accuracy and stability. In response to the abovementioned defects, a deep-learning-based music style classification method will be stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…https://www.indjst.org/ To identify melody, Standard MIDI files, as well as symbolic scores, are used (1,2) whereas our approach is based on MFCC features. Several pieces of research are performed that use MFCC in order to identify Music style, Musical instruments as well as Singer (4,5,8) . In the identification of singers, MFCC features are found to be better than the CRP features (8) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…https://www.indjst.org/ To identify melody, Standard MIDI files, as well as symbolic scores, are used (1,2) whereas our approach is based on MFCC features. Several pieces of research are performed that use MFCC in order to identify Music style, Musical instruments as well as Singer (4,5,8) . In the identification of singers, MFCC features are found to be better than the CRP features (8) .…”
Section: Resultsmentioning
confidence: 99%
“…To classify the songs into their respective genre CNN is also on spectrograms extracted from the songs (3) . MFCC-based CNN and RNN (Recurrent Neural Network) are used to determine the music style where 93.3% classification accuracy is achieved (4) .…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational and Mathematical Methods in Medicine has retracted the article titled “Research on Music Style Classification Based on Deep Learning” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Computational and Mathematical Methods in Medicine has retracted the article titled "Research on Music Style Classification Based on Deep Learning" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%